Early-life diet specificity is associated with long-lasting differences in apparent survival in a generalist predator - Nebel Carina; Ekblad Camilla; Balotari-Chiebao Fabio; Penttinen Ida; Stjernberg Torsten; Laaksonen Toni (WILEY, 2025)
1. Early-life conditions can have long-term fitness consequences. However, it is still unclear what optimal rearing conditions are, especially for long-lived carnivores. A more diverse diet ('balanced diet') might optimize nutrient availability and allow young to make experiences with a larger diversity of prey, whereas a narrow diet breadth ('specialized diet') might result in overall higher energy net gain. A diet that is dominated by a specific prey type (i.e. fish, 'prey type hypothesis') might be beneficial or detrimental, depending for example, on its toxicity or contaminant load.
2. Generalist predators such as the white-tailed eagle Haliaeetus albicilla provide an interesting possibility to examine the relationship between early life diet and long-term offspring survival. In the & ANGS;land Islands, an archipelago in the Baltic Sea, white-tailed eagles live in various coastal habitats and feed on highly variable proportions of birds and fish.
3. We use data from 21,116 prey individuals that were collected from 120 territories during the annual surveys, to examine how early-life diet is associated with apparent annual survival of 574 ringed and molecular-sexed eaglets. We supplement this analysis by assessing the relationships between diet, reproductive performance and nestling physical condition, to consider whether they are confounding with possible long-term associations.
4. We find that early-life diet is associated with long-term fitness: Nestlings that are fed a diverse diet are in lower physical condition but have higher survival rates. Eagles that are fed more fish as nestlings have lower survival as breeding-age adults, but territories associated with fish-rich diets have higher breeding success.
5. Our results show that young carnivores benefit from a high diversity of prey in their natal territory, either through a nutritional or learning benefit, explaining the higher survival rates. The strong relationship between early-life diet and adult survival suggests that early life shapes adult foraging decisions and that eating fish is associated with high costs. This could be due to high levels of contaminants or high competition for fish-rich territories. Long-lasting consequences of early-life diet are likely not only limited to individual-level consequences but have the potential to drive eco-evolutionary dynamics in this population.